THE INSTITUTIONAL CONDITIONS OF ENTREPRENEURSHIP DEVELOPMENT IN CENTRAL EUROPEAN COUNTRIES - Balcerzak, Adam P.; Rogalska, Elżbieta (Ekonomia i Prawo. Economics and Law, 2010)
Entrepreneurship is a key element influencing development of a country. Some experiences of last century and some theoretical works of new institutional economics show that an institutional system is the main determinant of entrepreneurship activity. The ineffective institutional order that usually goes with low effectiveness of governance results in high level of insecurity in business processes. All market actors are forced to deal with a burden of additional transaction costs in that case. It has an unfavorable influence on effectiveness of all businesses which must have significant influence on the level of entrepreneurship in an economy. The article aims at assessing condition and functioning of chosen elements of institutional system in Central and Eastern European countries in the field of creating the background for entrepreneurship. The article especially concentrates on comparative analysis of Poland with other countries of Central Europe and three highly developed countries USA, Germany and Japan treated as a benchmark.